2009
DOI: 10.1093/schbul/sbn170
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity-Based Cognitive Training in Schizophrenia: An Interim Report on the Effects 6 Months Later

Abstract: A total of 50 hours of neuroplasticity-based computerized cognitive training appears sufficient to drive improvements in verbal learning/memory and cognitive control that endure 6 months beyond the intervention, but a higher "dose" and more "broad-spectrum" training may be necessary to drive enduring gains in processing speed and global cognition. Training-induced cognitive improvement is related to enhanced functioning at 6 months. These data suggest that (1) higher and "broader" doses of cognitive training m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 43 publications
17
157
4
3
Order By: Relevance
“…Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up. Thus, the limited data available for this review suggest neuroplasticity-based interventions likely impact functional brain changes associated with basic perceptual/cognitive processes.…”
Section: Neuroplasticity-based Approachessupporting
confidence: 80%
“…Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up. Thus, the limited data available for this review suggest neuroplasticity-based interventions likely impact functional brain changes associated with basic perceptual/cognitive processes.…”
Section: Neuroplasticity-based Approachessupporting
confidence: 80%
“…7,43,44 We are currently investigating whether cognitive gains persist 6 months beyond the intervention and are associated with functional improvement, as previously observed in persistently ill adults. 45 Second, subjects were drawn from 2 university clinics, were of average IQ, and are not representative of community settings. We do not know if this intervention would be as effective in individuals with lower IQ or under 16 years of age.…”
mentioning
confidence: 99%
“…She has shown that the most-intensive training tested -100 hours -can improve global cognition for as long as six months after the training ends 5 . None of the groups showed a significant improvement in symptom severity or quality of life, but Vinogradov speculates that that was probably partly because there were only about ten patients in each group.…”
Section: Train Of Thoughtmentioning
confidence: 99%